Molecular mechanism of a new cardiac syndrome associated with a regulatory element deletion of chromosome 4q25. (25th November 2020) - Baudic, M; Murata, H; Le Scouarnec, S; Foucal, A; Lindenbaum, P; Ishikawa, T; Si-Tayeb, K; Gaborit, N; Makita, N; Makiyama, T; Shimizu, W; Vieyres, C; et al.
Abstract: Introduction: We identified a large family of 53 members of whom 22 present a new cardiac syndrome characterized by electrical disorders and developmental defects following an autosomal dominant model. Among the affected family members 6 are implanted with a pacemaker, 2 experienced syncope and one a sudden death at 43yo. Linkage analysis points, with high confidence, to the chromosome 4q25 region. This region is associated with the Ankyrin syndrome (mutation in ANK2) sharing partly the electrical defects observed in the affected family members. No mutation was found in the coding region of the 4q25 region as well as in the coding and non-coding part of the ANK2. Objective: Our aims are first to identity the responsible mutation present in this family and understand the molecular mechanisms leading to this new syndrome. Method: Whole genome sequencing (WGS) has been employed to identify genetic variants responsible for this syndrome. ChIP-seq and ATAC-seq were used for functional annotation and genome editing (CRISPR-Cas9) to generate iPS cellular models. Results: By WGS we uncovered a deleted region of 15kb in a gene desert area on 4q25, segregating in all affected relatives. Five other families (3 French and 2 Japanese) presenting the same phenotype show overlapping deletions. We generated human cardiac epigenetic data and identified among the 15kb deleted region a unique active enhancer region within the presence of a transcript factor CTCF binding site. Isogenic cell lines where the 15kb and the CTCF binding have been deleted are under investigation. Conclusion: We identified a new cardiac syndrome and for the first time a mutation located within a gene desert area leading to severe and complex cardiac disorders. We demonstrated the presence of a likely gene regulatory element. Experiments are ongoing to characterize the molecular mechanisms and consequence of the deletion on gene expression. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Pays de la loire - Etoiles montantes